Ginsenosides in Panax genus and their biosynthesis - Maoqi Hou; Rufeng Wang; Shujuan Zhao; Zhengtao Wang (Elsevier, 2021)
Ginsenosides are a series of glycosylated triterpenoids which belong to protopanaxadiol (PPD)-, protopanaxatriol (PPT)-, ocotillol (OCT)- and oleanane (OA)-type saponins known as active compounds of Panax genus. They are accumulated in plant roots, stems, leaves, and flowers. The content and composition of ginsenosides are varied in different ginseng species, and in different parts of a certain plant. In this review, we summarized the representative saponins structures, their distributions and the contents in nearly 20 Panax species, and updated the biosynthetic pathways of ginsenosides focusing on enzymes responsible for structural diversified ginsenoside biosynthesis. We also emphasized the transcription factors in ginsenoside biosynthesis and non-coding RNAs in the growth of Panax genus plants, and highlighted the current three major biotechnological applications for ginsenosides production. This review covered advances in the past four decades, providing more clues for chemical discrimination and assessment on certain ginseng plants, new perspectives for rational evaluation and utilization of ginseng resource, and potential strategies for production of specific ginsenosides.